DEVELOPING PROFESSIONAL REFLECTION IN IN-SERVICE LANGUAGE TEACHER EDUCATION: MECHANISMS AND CONDITIONS FOR SUSTAINABLE TEACHER GROWTH (Web of Teachers: Inderscience Research, 2026)
This article examines the development of professional reflection in in-service language teacher education. Drawing on a qualitative conceptual review and targeted narrative synthesis of literature, the paper explores how reflection can be transformed from a descriptive post-lesson activity into a structured, evidence-informed, and collaborative process of professional learning. The analysis identifies key mechanisms that support reflective development among in-service language teachers, including adult-oriented professional learning, structured reflective tasks, evidence-based classroom inquiry, language assessment literacy, collaborative reflection, mentoring, video-supported analysis, and reflective journals or portfolios. The article argues that these mechanisms are most effective when they operate as an integrated system rather than as separate professional development activities. Particular attention is given to the diagnostic function of reflection, as language teachers need to interpret learner performance, classroom interaction, task difficulties, and assessment evidence in order to make pedagogically justified decisions. The paper also emphasizes the importance of institutional conditions such as time, trust, feedback, and a non-evaluative professional culture.